Cataract surgery in patients with bilateral advanced age‐related macular degeneration: Measurement of visual acuity and quality of life. Issue 6 (June 2015) - Ma, Yingyan; Huang, Jiannan; Zhu, Bijun; Sun, Qian; Miao, Yuyu; Zou, Haidong
Abstract : Purpose : To measure the change in visual acuity and vision‐related quality of life in patients with both age‐related cataract and bilateral age‐related macular degeneration (AMD) after cataract surgery. Setting : Department of Ophthalmology, Shanghai General Hospital, Shanghai Jiao Tong University, Shanghai, China. Design : Prospective case series. Methods : Patients with age‐related cataract and bilateral advanced AMD who were diagnosed and treated between January 2006 and January 2012 were enrolled. The patients had successful phacoemulsification with foldable posterior chamber intraocular lens implantation. The corrected distance visual acuity (CDVA) and vision‐related quality of life measured by the Chinese‐version Low Vision Quality of Life (CLVQOL) questionnaire were collected. The Wilcoxon signed‐rank test was used to compare the differences. Binary logistic regression analysis was performed to explore potential factors associated with the change in CLVQOL scores. Results : Sixty eyes of 51 patients were included. The CDVA improved significantly (median difference 0.30 logMAR; range 0 to 1.38 logMAR; P < .001). The CLVQOL composite scores and the 4 subscale scores improved significantly (all P < .001). A greater increase in the CLVQOL scores was associated with inferior preoperative logMAR CDVA in the more severely affected eye (regression coefficient 3.36; P < .001). Conclusions : Cataract surgery improved visual acuity and the vision‐related quality of life in patients with both age‐related cataract and bilateral advanced AMD. Thus, it is beneficial for patients with coexistent advanced AMD to have cataract surgery. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.